Current Ratio (CR) Dan Debt to Asset Ratio (DAR) Terhadap Return On Asset (ROA) pada PT Indocement Tunggal Prakarsa Tbk Periode 2009-2018 - Diana Riyana Harjayanti; Puput Pujiati (Jurnal Madani: Ilmu Pengetahuan, Teknologi, dan Humaniora, 2020)
It is necessary to measure ratios that represent liquidity, solvability and profitability from one company. Related to this research use Current Ratio, Debt to Asset Ratio, Return On Asset Ratio at PT Indocement Tunggal Prakarsa Tbk. As one of largest cement factories in Indonesia. It is necessary to measure ratios that represent liquidity, solvability and profitability from one company. Related to this research use ratio of Current Ratio, Debt to Asset Ratio, Return On Assets at PT Indocement Tbk. as one of the largest cement factories in Indonesia. The data used in this study are secondary data from the company's 2009-2020 financial statements. Data processing stages are carried out by ensuring all data meet the classic assumption test, so that further stages are to measure influence of independent variabels : Current Ratio and Debt to Asset Ratio to dependent variabel : Return On Asset with multiple linear regression test, coefficient R determinant test, t test, F test.In addition, the results of the t test, the Current Ratio is partial influence to Return On Assets, but the Debt to Asset Ratio is not partial influence on Return On Assets. While from the results of the F test the Current Ratio and the Debt to Asset Ratio simultaneously influence to Return On Assets. Abstrak Untuk memastikan kondisi keuangan suatu perusahaan maka perlu dilakukan pengukuran dari rasio yang mewakili likuiditas, solvabilitas dan provitabilitas. Sehingga dalam penelitian ini dilakukan pengamatan terhadap rasio Current Ratio, Debt to Asset Ratio, Return On Asset pada PT Indocement Tbk. sebagai salah satu pabrik semen terbesar di Indonesia. Data yan digunakan dalam penelitian adalah data sekunder dari laporan keuangan perusahaan dari tahun 2009 -2018. Tahapan pengolahan data yang dilakukan dilakukan adalah memastikan semua data memenuhi standard uji asumsi klasik , agar selanjutnya dapat dilakukan tahapan pengolahan data untuk melihat pengaruh variabel bebas yaitu Current Ratio dan Debt to Asset Ratio terhadap variabel terikat yaitu Return On Asset melalui uji regresi linier berganda, uji koefisien determinasi R, uji t, uji F. Dari hasil uji t maka Current Ratio berpengaruh secara partial terhadap Return On Asset , namun Debt to Asset Ratio tidak berpengaruh secara partial terhadap Retun On Asset. Sedangkan dari hasil uji F maka Current Ratio dan Debt to Asset Ratio berpengaruh secara bersamaan terhadap Return On Asset. Kata Kunci : Current Ratio, Debt to Asset Ratio, Return On Asset, Kinerja PT Indocement Tunggal Prakarsa Tbk